Implementation of Corporate Governance on Environmental Performance and Bank Risk in Indonesia - Pradnyani, Ni Luh Putu Sri Purnama; Suartana, I Wayan; Sari, Maria Mediatrix Ratna; Budiasih, I Gusti Ayu Nyoman (Indonesian Journal of Sustainability Accounting and Management, 2023)
This study aims to examine the effect of corporate governance on environmental performance and the effect of environmental performance on bank risk in Indonesia from 2017 to 2021. Corporate Governance is measured by the board of directors and independent board, environmental performance is measured by the GRI Standard environmental category, and bank risk is measured by Non-Performing Loan (NPL). The research approach uses a quantitative approach that uses secondary data, namely annual financial reports, annual reports, and published bank sustainability performance. The total research population consists of 43 banks listed on the Indonesia Stock Exchange with a saturated sampling technique. The analytical tool used is path analysis. The results showed that corporate governance has a positive effect on bank environmental performance and environmental performance has a negative effect on bank risk. This study provides theoretical implications, namely deepening understanding of the relationship between CG practices and bank commitment to environmental sustainability, analyzing the relationship between environmental responsibility commitment and bank risk from the perspective of stakeholder theory. The practical implication is that companies must have programs and strategies to improve the bank’s environmental performance and banks need to include environmental risk in loan assessment. This study has an originality value of CG implications on environmental performance and bank risk in the observation period of the COVID period and the issuance of 51/POJK.03/2017.